Peran Kapabilitas Profesional dan Komunikasi terhadap Kinerja Sumber Daya Manusia Boosting Human Resource Performance: The Impact of Professional Capability and Effective Communication - Subiyanti, Eny; Khajar, Ibnu (VISA: Journal of Vision and Ideas, 2025)
This research aims to determine the influence of professional and communication capabilities on human resource performance. We believe that the research results will be useful in encouraging managers to take steps and strategies to improve employee performance. The research was conducted at the Department of Women's Empowerment, Child Protection, Population Control and Family Planning with a sample of 110 participants. The method in this research uses statistical methods and data collection methods using primary and secondary data. The reliability test uses Cronbach Alpha and the validity test uses correlation and discriminant. Testing uses the Partial Least Square (PLS) method. The research results show that: professional capability has a negative relationship with Human Resource Performance, Communication has a positive relationship with Human Resource Performance and Professional Capability has a positive relationship with Human Resource Performance through communication.